Neuman Systems Model With Nurse-Led Interprofessional Collaborative Practice. (January 2021) - Montano, Anna-Rae
The Neuman Systems Model was developed to create a structure to depict nursing clients as complex systems, in constant energy exchange with their environments, comprised of multiple interrelated parts. It has been widely used in practice, education, research, and administration. An analysis of the theory, based upon Meleis' methods, was conducted. The theory has high utility and a large circle of contagiousness despite its complexity, lack of teleology, and level of abstractness. Based upon this analysis, a new model entitled the Neuman Systems Model Perspective of Nurse-Led Interprofessional Collaborative Practice has been created to provide a framework for the care of community-dwelling older adults. As a first step in its development, this new model will be used to guide a mixed-methods study evaluating an interprofessional collaborative practice intervention for community-dwelling older adults.